1993
DOI: 10.1177/019459989310800611
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Undifferentiated Carcinoma: A Ray of Hope

Abstract: In 1987, we published a case series of a newly-described, highly malignant neoplasm, termed sinonasal undifferentiated carcinoma, in which treatment results were poor. In this updated study, we report the followup for the original three surviving patients and for six additional cases whose tumors were diagnosed between January 1987 and October 1991. These data suggest that the prognosis for patients with localized disease may be better than originally described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 4 publications
1
27
1
Order By: Relevance
“…SNUc, in addition to intestinal-like and squamous cell histologies, have been reported to correlate with poor prognosis in clinical trials (37,38). Conversely, in the present analysis, histological type did not affect patient prognosis; however, this may be due to the small sample size and the low number of SNUc cases included (3/30).…”
Section: Discussioncontrasting
confidence: 76%
“…SNUc, in addition to intestinal-like and squamous cell histologies, have been reported to correlate with poor prognosis in clinical trials (37,38). Conversely, in the present analysis, histological type did not affect patient prognosis; however, this may be due to the small sample size and the low number of SNUc cases included (3/30).…”
Section: Discussioncontrasting
confidence: 76%
“…2 A subsequent report from the same group suggested that there might be a role for treating patients with preoperative chemotherapy and radiation, with a better outcome seen in some patients without extensive brain involvement. 3 Many authors have subsequently advocated a multimodality approach incorporating surgery, radiotherapy, and chemotherapy. 3,4 Locoregional control has been difficult to achieve in most series, with the clinical picture often dominated by the manifestations of locoregional failure, although patients with SNUC also have a propensity to develop distant metastases.…”
mentioning
confidence: 99%
“…Based on the report by Deutsch et al 3 reporting prolonged disease-free survival in a few patients treated with a combination of radiotherapy, CAV (cyclophosphamide, doxorubicin, and vincristine) chemotherapy, and surgery, the generally poor results with initial surgery and the fact that patients frequently present with unresectable disease, a policy evolved of treating patients with locoregionally advanced SNUC with induction chemotherapy, followed by concurrent chemoradiation, reserving any surgery for patients with residual disease. We elected to treat patients initially with a regimen similar to the one we were using for locally advanced nasopharyngeal carcinoma at the time with three cycles of induction chemotherapy consisting of cisplatin (or carboplatin) and infusional 5-fluorouracil (5-FU ), followed by concurrent radiation with two cycles of platinum (cisplatin or carboplatin) in the first and last weeks of radiation.…”
mentioning
confidence: 99%
“…1 These tumors occur with enough frequency that specific treatment strategies have emerged. [2][3][4][5] The nonsinonasal neuroendocrine carcinomas (NSNECs), however, are represented predominantly by small cell undifferentiated carcinomas, followed by moderately differentiated (atypical carcinoid) carcinomas and well-differentiated (typical carcinoid) carcinomas. The NSNECs are rare enough that they are represented in the literature primarily by sporadic case reports.…”
mentioning
confidence: 99%